(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Our literature on the pathology of chronic recurrent aphthous aphthous stomatitis (CRAS) reveals that there are a number of scientific views on the etiopathogenesis of this pathology as a neurogenic, immune, infectious and allergic theory of origin. Other scientists are promoting the concept of the tendency of this pathology in favor of the endocrine theory or reactivity and resistance of the body [1, 2, 6, 7, 9, 10, 11, and 20].